Effect of Paclobutrazol on Biochemical and Yield Attributes of Chickpea (Cicer arietinum L.) - Panda, Sumanta; Mondal, Subhasis; Ali, Osman; Challam, Dawan Arkini (International Journal of Economic Plants, 2024)
The experiment was carried out during the rabi (winter) season ( 2nd week of November to last week of Feburary) of 2019 and 2020 at the District Seed Farm, ‘AB’ block, Kalyani at Bidhan Chandra Krishi Viswavidyalaya, Nadia, West Bengal to study the effect of paclobutrazol on the biochemical and yield attributes of chickpeas with yield. The experiment was laid down in a randomized block design having six treatments of a formulation of paclobutrazol 40% (0, 25, 35, 45, 55 and 65 ml ha-1) with each replicated four times and the experimental material for the study consisted of chickpea variety was JAKI 92-18. Results revealed that Paclobutrazol caused to decline in the leaf chlorophyll content and enhanced the accumulation of storage carbohydrates particularly starch in the leaf. Leaf soluble sugar content was lowest in the control (2.86) and all the treatments were significantly higher than the control in this respect. It caused to enhance the seed yield by enhancing the number of seeds plants-1 and improving the harvest index. The highest yield was obtained in paclobutrazol 35 ml ha-1 (2008 kg ha-1); other treatments with substantially higher yields than control were paclobutrazol 45 ml ha-1 (1783 kg ha-1), and paclobutrazol 25 ml ha-1 (1692 kg ha-1). Hence, foliar application of Paclobutrazol @ 35 ml l-1 may be most effective in augmenting the yield attributes and yield of chickpea during rabi season.